Atmospheric Sciences Perspectives on Integrated, Coordinated, Open, Networked (ICON) Science. Issue 2 (16th February 2022) - Blanken, P. D.; Brunet, D.; Dominguez, C.; Goursaud Oger, S.; Hussain, S.; Jain, M.; Koren, G.; Mu, Y.; Ray, P.; Saxena, P.; Sonwani, S.; Sur, D.
Abstract: This collaborative article discusses the opportunities and challenges of adopting integrated, coordinated, open, and networked (ICON) principles in atmospheric sciences. From the global nature of the atmosphere, there has always been a need for atmospheric science to be an ICON science. With the help of evolving technology, it is possible to go further in implementing and spreading the ICON principles for productive global collaboration. In particular, technology transfer and applications could be approached with reproducibility in mind, and data‐sharing infrastructure could enable easier and better international collaboration. There are, however, various challenges in following the ICON principles in the acquisition, quality control, and maintenance of data, and the publication of results in a systematic way. Moreover, the extent of such issues varies geographically and hence poses different challenges to implementing ICON principles. In this commentary article, we briefly state our perspectives on the state of ICON, challenges we have met, and future opportunities. Furthermore, we describe how atmospheric science researchers have benefited from these collaborative multi‐dimensional approaches that fulfill the core goal of ICON. Plain Language Summary: The integrated, coordinated, open and networked (ICON) principles help researchers generate and disseminate knowledge in the atmospheric sciences. These principles can be achieved by designing strategies for data collection, analysis, modeling, and interpretation, and by involving scientists and stakeholders worldwide to maximize the benefit to science and society. However, challenges in openly sharing data produced in field campaigns or handling large volumes of atmospheric data remain. Therefore, coordinated and networked efforts are needed worldwide. Key Points: Atmospheric scientists have benefited from the principles of integrated, coordinated, open, and networked science Effective coordination in data collection, monitoring, and modeling can help achieve substantial progress in atmospheric science Progress in global collaboration is possible through sharing infrastructure and enhanced support for scientists from lower‐income countries